The disabilities of the arm, shoulder, and hand scale in the evaluation of disability - A literature review - Wajngarten, Danielle [UNESP]; Campos, Juliana Alvares Duarte Bonini [UNESP]; Garcia, Patrícia Petromilli Nordi Sasso [UNESP] (Mattioli1885, 2017)
Background: Work-related musculoskeletal disorders (WRMDs) interfere with workers' productivity and quality of life. Thus, early detection of disabilities caused by WRMDs is vital for preventing the aggravation of symptoms. Early detection AIDS and is aided by educational and preventive programs. WRMDs can be detected using the Disabilities of the Arm, Shoulder and Hand (DASH) Scale. Objectives: The present study aimed to review the literature on the application of the DASH Scale through a consideration of the cultural adaptation process and an evaluation of the scale's psychometric properties. Methods: The literature review was conducted using the terms disabilities, musculoskeletal disorders, DASH questionnaire and upper limbs. Results: Forty-eight articles were collected, and these included only articles available in English which contained the full version of the DASH Scale and which focused on the evaluation of its psychometric properties (n=25). Conclusion: Most of the studies partially evaluated the psychometric properties of the DASH instrument; however, these properties were typically evaluated using only a correlation analysis involving other instruments.
Keywords: Correlation analysis; DASH; Factor analysis; Reliability; Validity